Sintesis, Karakterisasi Struktur dan Sifat Optik Nanopartikel Hidroksiapatit/Magnetit - Yuanita Amalia Hariyanto; Ahmad Taufiq; Sunaryono Sunaryono (Universitas Negeri Malang, 2018)
Hydroxyapatite becomes one of the promising biomaterials to be applied in medical fields due to its special performances such as biocompatible and non-toxic. So that it to improve performance of hydroxyapatite, it is necessary to develop the hydroxyapatite by compositing with magnetite. In this work, the hydroxyapatite/magnetite was synthesized using precipitated method and characterized using XRD, FTIR, SEM-EDAX, and UV-Vis spectrometer for investigating the detailed structure, functional group, morphology, and band gap energy of the prepared sample. The results show that the sample has two phases with high purity i.e. hydroxyapatite and magnetite without any impurities. The data analysis using the Scherrer’s equation shows that the hydroxyapatite/magnetite has particle size about 10 nm. Meanwhile, the data analysis using FTIR indicates the presence of atomic bond from both of hydroxyapatite and magnetite. Morphologically, it is seen that the sample has an agglomeration in the nanometric size. Interestingly, the hydroxyapatite/magnetite has a band gap energy of about 3.8 eV which is in the range of the band gap energy of hydroxyapatite and magnetite.DOI: http://dx.doi.org/10.17977/um024v3i12018p016